Metal Fume Fever among Galvanized Welders - Wardhana Wardhana; E.A. Datau (Acta Medica Indonesiana)
The metal fume fever (MFF) is an inhalation fever syndrome in welders of galvanized steel, who join and cut metal parts using flame or electric arc and other sources of heat. Inhalation of certain freshly formed metal oxides produced from welding process can cause MFF as an acute self-limiting flulike illness. The most common cause of MFF is the inhalation of zinc oxide (ZnO). The inhalation of ZnO particles can provoke a number of clinical responses of which accompanied by changes in composition of bronchoalveolar lavage (BAL) fluid, including early increase in pro-inflammatory cytokines, inflammatory marker, and recruitment of inflammatory cells in the lungs. The MFF is characterized by fever, cough, sputing, wheezing, chest tightness, fatique, chills, fever, myalgias, cough, dyspnea, leukocytosis with a left shift, thirst, metallic taste, and salivations. The diagnosis of MFF diagnosis is based on clinical finding and occupational history. The symptoms resolved spontaneously. The treatment of MFF is entirely symptomatic, no specific treatment is indicated for MFF. The mainstay of management of MFF is prevention of sub-sequent exposure to harmful metals. Including public and physician awareness of MFF may help to reduce the occurrence of the disease.